1977
DOI: 10.1002/ijc.2910190213
|View full text |Cite
|
Sign up to set email alerts
|

Polyoma genome transcription in transformed mouse cells growing in culture and as tumors in syngeneic mice

Abstract: The strands of the polyoma genome coding for early and late viral RNA were separated by means of asymmetric cRNA synthesized under high salt conditions by Escherichia coli RNA polymerase. Each strand was then employed in RNA-DNA hybridization experiments to determine the degree to which it is transcribed in transformed cells under several conditions. Except for a concanavalin-A-selected revertant, approximately one-quarter of the early strand was expressed in all of the situations investigated. In contrast, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…That large T-antigen plays no role in maintaining the transformed phenotype was further suggested by other observations. First, several investigators failed to find mRNA sequences complementary to the distal portion of the polyoma viral early region in some transformed cell lines (2,14,25). Moreover, large T-antigen could not be detected in a number of cell lines transformed by the virus (19).…”
mentioning
confidence: 99%
“…That large T-antigen plays no role in maintaining the transformed phenotype was further suggested by other observations. First, several investigators failed to find mRNA sequences complementary to the distal portion of the polyoma viral early region in some transformed cell lines (2,14,25). Moreover, large T-antigen could not be detected in a number of cell lines transformed by the virus (19).…”
mentioning
confidence: 99%
“…Mutants containing lesions that map within the early region either fail to transform cells completely [the host-range transformation-defective mutants (1,2)] or are temperature sensitive for the establishment of transformation and in some cases its maintenance [the tsa mutants (3)(4)(5)(6)]. Moreover, RNA complementary to only the "E" strand of the early region of the viral DNA is always detected in transformed cells (7)(8)(9)(10), and these cells inevitably contain tumor antigens (T antigens), proteins encoded by the early region of the virus (11)(12)(13).…”
mentioning
confidence: 99%
“…Several analyses of virus-specific RNA in polyoma-transformed cells revealed that some lines either lack or contain smaller amounts of those RNA sequences that are transcribed from the distal part of the early region (7,9,10 (15). Transfections with viral and plasmid DNAs were performed as described (16), using intact plasmids purified on CsCl gradients.…”
mentioning
confidence: 99%